1990
DOI: 10.1007/bf00035012
|View full text |Cite
|
Sign up to set email alerts
|

Control of misses in oxygen evolution by the oxido-reduction state of plastoquinone in Dunaliella tertiolecta

Abstract: The way misses happen in oxygen evolution is subject to debate (Govindjee et al. 1985). We recently observed a linear lowering of the miss probability with the flash number (Meunier and Popovic 1989). Therefore, we investigated in Dunaliella tertiolecta the link between the average miss probability and the redox state of plastoquinone after n flashes. The effect of flashes was to oxidize the plastoquinone pool; we found that the oxidation of plastoquinone highly correlated (linear regression: R (2)=0.996) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
8
2
Order By: Relevance
“…Our results show a steady linear variation of the miss probability, correlated to a steady, progressive oxidation of plastoquinone (Meunier and Popovic 1989). However, those reported by Lavorel and Lemasson 1976) show erratic or semi-oscillatory (period 2) variations.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…Our results show a steady linear variation of the miss probability, correlated to a steady, progressive oxidation of plastoquinone (Meunier and Popovic 1989). However, those reported by Lavorel and Lemasson 1976) show erratic or semi-oscillatory (period 2) variations.…”
Section: Resultscontrasting
confidence: 45%
“…If the oxygen production is averaged over any five other precedent flashes, excepted when the third flash is included, the result is smaller than one. This shows We investigated in another work (Meunier and Popovic 1989) the effects of flashes on the plastoquinone pool. Using a 10 Hz flash frequency, as in the 02 evolution measurements, we observed that flashes oxidized the plastoquinone pool.…”
Section: Resultsmentioning
confidence: 99%
“…The large oscillations, displaying a periodicity of four, are obviously associated to electron fluxes through acceptor and donor sides of PS II which lead to both reoxidation of the plastoquinones molecules and changes in the distribution of the S-states. This modest effect of the pBQ treatment on the pattern of O2-emission differed from that obtained with Chlorella in anaerobic conditions (Greenbaum and Mauzerall 1976) and with Dunaliela in aerobiosis (Meunier and Popovic 1990). In these two materials, addition of pBQ restored oscillations of 02-emission not existing in control dark-adapted cells.…”
Section: Flash Pattern Of 02-evolution For the Interpretation Of The contrasting
confidence: 38%
“…It is possible to control the lifetime of $3 by keeping the PS II electron acceptors oxidized (Styring and Rutherford 1987;Meunier and Popovic 1990). This is especially true in thylakoid preparations, and at low temperatures, long-lived $3 (stable for a few minutes) that is affected by ADRY agents has been observed (Schmid et al 1994).…”
Section: Discussionmentioning
confidence: 99%